REVIEW OF PUBLIC EDUCATION PROGRAM NATIONAL GALLERY OF INDONESIA, 2015-2022 CASE STUDY - Paramita Putri, Anggira
Museums become a means and infrastructure to communicate the history of the past and develop the future. Museums basically perform two major functions, namely as a place of cultural preservation both tangible and intangible, and as a source of cultural information. So that the function as an educational service cannot be separated from an institution, both government-run and private museums. The problem that arises in museums managed by the government, the private sector and art events in Indonesia in various countries is the appreciation of works of art, the lack of public education programs in socializing how to appreciate good works. Many appreciators respond excessively when appreciating artworks. This has caused anxiety so that Galeri Nasional Indonesia created a public education program called "Becoming the Greatest Art Appreciator" starting from 2015 until now 2022. This is done by GNI as a government institution in charge of providing educational services and also maintaining state collections. The research will examine the planning, implementation, and evaluation of the public education program "Becoming the Greatest Art Appreciator" in the 2015- 2022 period. The perspective of "New Museology" on the public education program run by GNI "Becoming the Greatest Art Appreciator" in the 2015-2022 period. This qualitative research uses archival data processing and interviews with sources. The "New Museology" theory, especially in the aspects of mediation, continuing education, and evaluation, emphasizes the interrelated variables between management theory, museum education theory, and communication theory. GNI became the pioneer of the "Becoming the Greatest Art Appreciator" program because the program was only run by GNI, the museum managed by the Ministry of Education and Culture had never run a similar program. Based on data and interviews from 2015-2022, the planning and implementation of the "Becoming the Greatest Art Appreciator" program is carried out repeatedly, only the place of implementation and exhibitions are different, participation in the implementation of the program must be able to involve the public at large not only limited to the junior / senior high school level, evaluation of the program has not been carried out because the purpose of the "Becoming the Greatest Art Appreciator" program is to make participants an agent for changes in attitudes and behavior, the need for a communication exchange process to cause the effect of the message conveyed. This research concludes that the "Becoming the Greatest Art Appreciator" program is not yet procedurally ideal in the principles of "New Museology", especially in the aspects of mediation, continuing education, and evaluation